Analisis Penelitian Rute Transportasi Darat Balikpapan-Samarinda: Analysis Of Land Transportation Route Choice Balikpapan-Samarinda - Makaingat, Syaulla Nefertity; Hasanuddin, Akhmad; Maliq, Tatang Maulana (Media Ilmiah Teknik Sipil, 2024)
The existence of one of the transportation infrastructure in Indonesia, namely the Balikpapan-Samarinda Toll Road, can be traveled by one route through Soekarno-Hatta National Road with a distance of 114 km, while after the realization of the Balikpapan-Samarinda toll road, it can be reached with a distance of 97.99 km with a travel time of only 1 hour 12 minutes and with a tariff of Rp. 146,500 for class 1 (one) vehicles through the Manggar toll gate to Mahkota Bridge 2 (PTJBS, 2021). With the addition of one traffic route from Balikpapan City to Samarinda City or vice versa, of course travelers can choose a travel route that can reduce distance. However, not all passengers choose the same route, many factors can influence the route choice by passengers. This research is conducted by interviewing route users and obtaining travel characteristics and route selection model with attributes of travel cost, and travel time. From the regression results, the travel cost utility equation Ujt - Ujn = 0.00002 (X1) - 3.2886 and the travel time utility equation Ujt - Ujn = 0.0876 (X2) - 2.9795. Both attributes produce a min (-) utility function model, which means that the smaller the difference in travel costs and times, the greater the potential for route users to move from Jl. Nasional to Jl. Tol.